Fetomaternal Hemorrhage following Placement of an Intrauterine Pressure Catheter: Report of a New Association - Fadi G. Mirza; Harshwardhan M. Thaker; Wendy L. Flejter; Mary E. D’Alton (Case Reports in Obstetrics and Gynecology)
Fetomaternal hemorrhage (FMH) can be associated with significant perinatal mortality. Our review of the literature did not identify any cases of FMH following placement of an intrauterine pressure catheter (IUPC). In our case, an IUPC was inserted in a patient undergoing induction of labor at term. Fetal bradycardia ensued shortly after placement, warranting an emergent cesarean delivery. Severe neonatal anemia was identified, and evaluation of maternal blood was consistent with massive FMH. This is the first reported association between FMH and IUPC placement. If this relationship is validated in future reports, appropriate changes in clinical practice may be warranted.